91.6k views
5 votes
Subtract the polynomial below.
(12x² - 3x - 12) - (16x² - x + 1)

User Mike Ottum
by
5.2k points

1 Answer

4 votes

Explanation:

(12x^2 - 3x - 12) - (16x^2 - x + 1)

You can use the distributive formula to solve this equation:

12x^2 - 3x - 12 - 16x^2 + x - 1

Add or subtract by the common terms:

12x^2 - 16x^2 = -4x^2

-3x + x = -2x

-12 - 1 = -13

Then, put the answers back to an equation to get your results:

= -4x^2 - 2x - 13

Hope this helped!!

~A̷l̷i̷s̷h̷e̷a̷♡

User Claes Wikner
by
5.3k points